The Puzzling Pattern of Multiple Job Holding across U.S. Labor Markets. - Hirsch, Barry T.; Husain, Muhammad M.; Winters, John V. (Southern Economic Journal, 2017)
Multiple job holding (MJH) rates differ substantially across U.S. regions, states, and metropolitan areas. Rates decrease markedly with respect to labor market size. These patterns have been largely overlooked, despite being relatively fixed over (at least) the past 20 years. This article explores explanations for these persistent differences. We account for roughly two-thirds of the mean absolute deviation in MJH across local labor markets (MSAs). The results suggest that variation in MJH across labor markets is driven by labor market differences in job opportunities and worker preferences. Most important in explaining variation in MJH are MSA industry and occupation structure, ancestry shares, commute times, and, to a lesser extent, labor market churn.